Association between Muscle Mass and Body Mass Index in Elderly Diabetic Patients Attending Tertiary Care Center in Bangalore, India - Sowbarnika Palanisami; Vasudha Kulkarni (University Library System, University of Pittsburgh, 2016)
Background: Sarcopenia is a disorder causing age-related loss of muscle mass. Its multifaceted nature has been linked to an increased risk of disability and mortality. Equally, obesity is a well-known risk factor for a host of disorders. A combination of sarcopenia and obesity in elderly diabetics can synergistically lead to increased insulin resistance and risk of metabolic syndrome. This study aimed to identify the association between sarcopenia and obesity in elderly diabetic patients by a cost-effective anthropometric method. Methods: A case-control study was conducted from January 2016 to April 2016 at Dr. B. R. Ambedkar Medical College in Bangalore. Height, weight, mid-arm circumference, and triceps skin fold thickness of 112 diabetic patients and 131 healthy adults were measured. Descriptive statistical analysis and multiple linear regression analysis were carried out. Results: 26.8% of male and 76.8% of female diabetic patients were obese (body mass index ≥25 kg/m2). Incidence of sarcopenia (muscle mass one standard deviation smaller than healthy reference population, cut-off value for diabetic males being <9.79 kg/m2 and for diabetic females <8.53 kg/m2) were 12.5% in male diabetic patients and 5.4% in female diabetic patients. Conclusion: Sarcopenia and obesity are co-morbid illnesses which can cause functional and metabolic impairments in elderly diabetic patients. There exists a moderate association between muscle mass and body mass index. Loss of muscle strength (dynapenia), rather than loss of muscle mass (sarcopenia), is closely associated with disabilities in these patients.